The future was now : madmen, mavericks, and the epic sci-fi summer of 1982 - Nashawaty, Chris (Flatiron Books, 2024)
"From legendary entertainment journalist and author of Caddyshack comes a rollicking history of 1980s cinema-how eight legendary sci-fi films changed Hollywood forever In the summer of 1982, eight science fiction films were released within six weeks of one another. E.T., Tron, Star Trek: Wrath of Khan, Conan the Barbarian, Blade Runner, Poltergeist, The Thing, and Mad Max: The Road Warrior changed the careers of some of Hollywood's now biggest names-altering the art of movie-making to this day. In The Future Was Now, Chris Nashawaty recounts the riotous genesis of these films, featuring an all-star cast of Hollywood luminaries and gadflies alike: Steven Spielberg, at the height of his powers, conceives E.T. as an unlikely family tale, and quietly takes over the troubled production of Poltergeist, a horror film he had been nurturing for years. Ridley Scott, fresh off the success of Alien, tries his hand at an odd Philip K. Dick story that becomes Blade Runner-a box office failure turned cult classic. Similar stories arise for films like Tron, Conan the Barbarian, and The Thing. Taken as a whole, these films show a precarious turning-point in Hollywood history, when baffled film executives finally began to understand the potential of high-concept films with a rabid fanbase, merchandising potential, and endless possible sequels. Expertly researched, energetically told, and written with an unabashed love for the cinema, The Future Was Now is a chronicle of how the revolution sparked in a galaxy far, far away finally took root and changed Hollywood forever"--